Cover Image, Volume 40, Issue 6. Issue 6 (8th October 2020) - Farhan, Mohd; Silva, Marta; Li, Shuai; Yan, Fengxia; Fang, Jiankang; Peng, Tangming; Hu, Jim; Tsao, Ming‐Sound; Little, Peter; Zheng, Wenhua
Abstract : The cover image is based on the Review Article The role of FOXOs and autophagy in cancer and metastasis‐Implications in therapeutic development by Mohd Farhan et al., https://doi.org/10.1002/med.21695 .